Exploring cultural values through expressions of shame: an appraisal analysis of Japanese novels - Dewi Puspitasari; Eva Tuckyta Sari Sujatna; Inu Isnaeni Sidiq; Susi Yuliawati (Penerbit Universiti Kebangsaan Malaysia, 2025)
Shame is not only viewed as an individual experience but also as a cultural phenomenon. In this regard, shame is perceived as an evaluative action because the shame experienced by an individual can be predicted through appraisals within the discourse influenced by their values. This research aims to explore Japanese cultural values reflected through expressions of shame. The data sources are four novels by a young author, Rurika Suzuki. These novels represent the adolescent world in Japan, as they are constructed from a teenager's perspective. Utilizing a qualitative methodology, this study identifies the construction of social bonds from discourse containing expressions of shame and explains the cultural values embedded within it by applying the concepts of haji no bunka 'shame culture', appraisal theory, and affiliation theory. The findings indicate that the expressions of shame reflect Japanese cultural values, including amae 'interdependence', shuudan ishiki 'group awareness', sekentei 'reputation', and honne-tatemae 'true feelings-public presentation'. These cultural values are interpreted through graduation, attitude, and ideation resources. This research concludes that the shame experienced by adolescents can be both negative and positive. It is considered negative when shame arises from concerns about negative judgments from others; it is viewed as positive when shame emerges as a reaction to praise or as a form of politeness. The current study shows that an analytical framework can be applied to conduct an in-depth analysis of the cultural values that are discursively negotiated within discourse through appraisal analysis.